Development of single and mixed isoform selectivity PI3Kδ inhibitors by targeting Asn836 of PI3Kδ. Issue 19 (1st October 2016) - Miller, Michelle S.; Mountford, Simon J.; Pinson, Jo-Anne; Zheng, Zhaohua; Künzli, Marco; Patel, Vanit; Hogg, Simon J.; Shortt, Jake; Jennings, Ian G.; Thompson, Philip E.
Graphical abstract: Abstract: A series of PI3Kδ inhibitors derived from the pan-PI3K inhibitor ZSTK474 was prepared that target a non-conserved region of the catalytic site. Dependent upon the substituents present, these analogues show different levels of isoform selectivity and sensitivity to the mutation N836D in PI3Kδ. As a marker of 'on-target' activity and permeability, a selection of the most potent PI3Kδ inhibitors were shown to inhibit pAkt production in the Nawalma Burkitt lymphoma cell line.